Preparation and application of nano-silver-loaded silicon dioxide composite fiber antibacterial material
Through the antibacterial material of nano-silver-loaded silica composite fiber, the problem of tobacco flavors and fragrances being susceptible to microbial contamination during the production process is solved, and the long-term bactericidal and quality stability of the fragrance is achieved.
Patent Information
- Application Number
- CN202411706557.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
Tobacco flavors and fragrances are susceptible to microbial contamination during storage and production, resulting in product spoilage and deterioration and short shelf life, affecting product quality stability.
Silica composite fiber antibacterial material loaded with nanosilver is used to prepare silica fibers by electrostatic textile method, and nanosilver is loaded on its surface to form a long-term bactericidal antibacterial material. During the sterilization process of tobacco flavors, this material realizes the sterilization effect of the fragrance by installing a filter net of nano-silver-loaded silica fibers at the feed and discharge ports of the turnover tank.
Effectively prevent microbial contamination of tobacco flavors, extend the shelf life of the product, improve product quality stability, and the antibacterial material is easy to use in multiple scenarios and is easy to separate and process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tobacco flavors and fragrances, and in particular to the preparation and application of a nano-silver-loaded silica composite fiber antibacterial material. Background Art
[0002] At present, market competition is constantly expanding, and competition among tobacco companies is becoming increasingly fierce. In order to effectively develop high-quality products in the fierce market competition, tobacco companies need to develop core technologies based on their own characteristics. Among them, tobacco flavors and fragrances, as an indispensable raw material in the production process of cigarettes, are related to the composition of the characteristic flavor of cigarette brands, and their formula composition is also one of the core technologies of tobacco industry enterprises. The quality control and key technology research of tobacco flavors and fragrances are increasingly attracting the attention of enterprises.
[0003] Tobacco product processing companies need a wide variety of flavors and fragrances, and their quality stability is easily affected by factors such as raw materials and processing. The quality of tobacco flavors and fragrances determines the quality of the final cigarette products, and has received extensive attention from tobacco industry manufacturers. In recent years, it has been found that during the storage and production process of tobacco flavors and fragrances, raw materials and finished tobacco flavors and fragrances are susceptible to microbial contamination, which leads to the corruption and deterioration of some products, resulting in a short shelf life. In order to ensure product quality, it is imperative to develop antibacterial technology for tobacco flavors and fragrances.
[0004] As an effective antibacterial agent, metallic silver has the advantages of broad-spectrum antibacterial, high temperature resistance, strong durability, and excellent biocompatibility. Metallic silver nanoparticles have size effects and higher specific surface area, higher antibacterial activity, and have significant advantages such as being difficult to develop drug resistance, non-toxic or low-toxic, and heat-resistant. They have been used in the fields of food and medicine. Antibacterial materials loaded with nanosilver on a silica substrate are easy to operate, easy to separate and process, and have long-lasting antibacterial properties in the process of antibacterial tobacco flavors and fragrances. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a preparation and application of a nanosilver-loaded silica composite fiber antibacterial material. Aiming at the risk of microbial contamination during the use of tobacco flavors and fragrances, which leads to adverse factors affecting the stability of product quality, the present invention uses nanosilver as a bactericidal source and loads it on a silica fiber material, and it is expected to obtain an antibacterial material that can achieve long-term bactericidal effects and can be used in multiple scenarios.
[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions:
[0007] The nanosilver-loaded silica composite fiber antibacterial material of the present invention is prepared by loading nanosilver onto the surface of silica fiber produced by electrostatic spinning. Nanosilver is used as an antibacterial source, and silica fiber is used as a carrier to provide loading sites. Using silica as a carrier makes it easy to separate from the antibacterial target and convenient to use.
[0008] A nanosilver-loaded silica composite fiber antibacterial material comprises a silica fiber carrier and loaded nanosilver, wherein the nanosilver is loaded on the surface of the silica fiber carrier, and the loading amount of the nanosilver is 0.05-0.5%.
[0009] Preferably, in the above technical solution, the silica fiber carrier is prepared by electrospinning.
[0010] A method for preparing a nanosilver-loaded silica composite fiber antibacterial material comprises the following steps:
[0011] (1) Preparation of silica fiber: a certain amount of tetraethyl orthosilicate, methanol, N,N-dimethylformamide and nitric acid solution are mixed, polyvinyl pyrrolidone and polyacrylamide are added after stirring evenly, and stirring is continued for more than 2 hours to obtain an electrospinning precursor solution, and the spinning precursor solution is extracted in a micro-syringe pump, dried and then calcined, and the silica fiber is obtained after cooling;
[0012] (2) Preparation of silver-containing solution: Add an equal volume of 0.2 mol / L silver nitrate dropwise to a 0.1 mol / L sodium bicarbonate solution, mix well, add polyethylene glycol and sodium citrate, and continue stirring until completely dissolved to obtain a silver-containing solution;
[0013] (3) Preparation of nanosilver-loaded silica composite fiber antibacterial material: The silica fiber of step (1) is placed in the silver-containing solution of step (2), placed in a high-pressure reaction device, and subjected to a hydrothermal reaction to obtain the nanosilver-loaded silica composite fiber antibacterial material.
[0014] Preferably, the above technical solution further includes the following steps:
[0015] (5) Molding treatment: The obtained nanosilver-loaded silica fibers are prepared into a spun filter for use.
[0016] Preferably, in the above technical scheme, in step (1), the volume ratio of tetraethyl orthosilicate, methanol, N,N-dimethylformamide and nitric acid solution is (20-25):(15-20):1:0.1, the concentration of nitric acid is 0.1-0.4 mol / L, the molecular weight of polyvinyl pyrrolidone is 120-150W, and the added amount accounts for 1-2wt% of the mixed solution, and the molecular weight of polyacrylamide is 120-140W, and the added amount accounts for 1-2wt% of the mixed solution.
[0017] Preferably, in the above technical solution, in step (1), the parameter conditions for spinning the precursor liquid in the injection pump are: the spinning precursor liquid feeding speed is 3-6mL / h, the voltage is 23-26kV, the solidification acceptance distance is 18cm, and the inner diameter of the needle is 0.62cm.
[0018] Preferably, in the above technical solution, in step (1), after the precursor liquid is extracted, the drying conditions are vacuum drying at 100°C for 4 hours, the calcination temperature is 550°C-650°C, the heating rate is 4°C / min, and the heat preservation is 2 hours.
[0019] Preferably, in the above technical solution, in step (2), the weight ratios of the mixed solution to polyethylene glycol and sodium citrate are 1:0.01-0.05 and 1:0.1-0.6 respectively.
[0020] Preferably, in the above technical solution, in step (3), the weight ratio of silica fiber to silver-containing solution is 1:2-5.
[0021] The invention discloses an application of a nano-silver-loaded silica composite fiber antibacterial material in the sterilization of tobacco flavors and fragrances. The nano-silver-loaded silica composite fiber antibacterial material is a nano-silver-loaded silica composite fiber antibacterial material prepared according to the above preparation method.
[0022] An application of a nanosilver-loaded silica composite fiber antibacterial material in the sterilization of tobacco flavors and fragrances, the application being: transferring tobacco flavors and fragrances into a turnover tank, and installing a filter mesh made of nanosilver-loaded silica fiber at the feed and discharge ports of the turnover tank. The finished tobacco flavors and fragrances are brought into contact with the nanosilver during the feeding and discharge processes, thereby achieving a sterilization effect. The nanosilver-loaded silica fiber filter mesh at the feed and discharge ports of the turnover tank is regularly recovered, ultrasonically cleaned with water, propylene glycol, and ethanol for 20-30 minutes, and then dried for continued use.
[0023] The above technical solution of the present invention has the following beneficial effects:
[0024] In the present invention, the nanosilver antibacterial source is loaded onto the surface of the silica fiber, and the fiber is easy to be made into other products, so it is easy to use in various production scenarios and is easy to separate. At the same time, loading on the silica fiber also increases the contact between the nanosilver and the antibacterial target. DETAILED DESCRIPTION
[0025] Various exemplary embodiments of the present invention will now be described in detail. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless specifically stated otherwise.
[0026] Unless otherwise specified, the reagents used in this application are all commercially available or obtained through commercial channels, or can be prepared by referring to existing chemical methods.
[0027] Example 1
[0028] (1) Preparation of antibacterial silica composite fiber material loaded with nanosilver:
[0029] By volume, 20 parts of tetraethyl orthosilicate, 20 parts of methanol, 1 part of N,N-dimethylformamide, and 0.1 parts of nitric acid solution are mixed, stirred evenly, and polyvinyl pyrrolidone and polyacrylamide are added, and stirring is continued for more than 2 hours to prepare the spinning precursor solution. In the injection pump, the spinning precursor feed rate is 3-6mL / h, the voltage is 23-26kV, the curing acceptance distance is 18cm, and the inner diameter of the needle is 0.62cm. After the precursor solution is extracted, the drying conditions are vacuum drying at 100℃ for 4h, the calcination temperature is 550℃, the heating rate is 4℃ / min, and the temperature is kept for 2h. After cooling, silica fiber is obtained. Among them, the molecular weight of polyvinyl pyrrolidone is 120-150W, and the amount added accounts for 1-2wt% of the mixed solution, and the molecular weight of polyacrylamide is 120-140W, and the amount added accounts for 1-2wt% of the mixed solution.
[0030] Add an equal volume of 0.2 mol / L silver nitrate dropwise into a 0.1 mol / L sodium bicarbonate solution, mix well and then add polyethylene glycol and sodium citrate. The weight ratios of the mixed solution to polyethylene glycol and sodium citrate are 1:0.01 and 1:0.1 respectively. Continue stirring until completely dissolved to obtain a silver-containing solution.
[0031] The silica fiber was placed in a silver solution, the weight ratio of the silica fiber to the silver solution was 1:2, and after a hydrothermal reaction in a high-pressure reaction device, nanosilver was loaded on the surface of the silica fiber. The conditions for the hydrothermal reaction were heating to 250°C, heating rate of 2°C / min, and keeping warm for 10 hours.
[0032] The silica fibers loaded with nanosilver are spun into filter meshes for use.
[0033] (2) Finished tobacco products are treated with flavors and fragrances:
[0034] After being prepared according to the product formula, the finished Golden Leaf (Tianxingjian) flavors and fragrances (provided by Henan China Tobacco Zhumadian Cigarette Factory) need to be transferred to the turnover tank, and the filter screen made of silica fiber loaded with nanosilver is installed at the feeding and discharging ports of the turnover tank. During the feeding and discharging process, the finished tobacco flavors and fragrances come into contact with nanosilver, thus achieving a sterilization effect.
[0035] The antibacterial properties of the treated finished tobacco flavors and fragrances were tested, and the results are shown in Table 1.
[0036] (3) Recycling of antibacterial materials:
[0037] The filter screens made of silica fibers loaded with nano-silver at the feed and discharge ports of the turnover tank are regularly recovered, ultrasonically cleaned with water, propylene glycol and ethanol for 20-30 minutes respectively, and can be used again after drying.
[0038] Table 1 Antibacterial test results
[0039]
[0040] Example 2
[0041] (1) Preparation of antibacterial silica composite fiber material loaded with nanosilver:
[0042] By volume, 25 parts of tetraethyl orthosilicate, 15 parts of methanol, 1 part of N,N-dimethylformamide, and 0.1 parts of nitric acid solution are mixed, and polyvinyl pyrrolidone and polyacrylamide are added after stirring evenly, and stirring is continued for more than 2 hours to prepare the spinning precursor solution. In the injection pump, the spinning precursor feed rate is 6mL / h, the voltage is 26kV, the curing acceptance distance is 18cm, and the inner diameter of the needle is 0.62cm. After the precursor solution is extracted, the drying conditions are vacuum drying at 100℃ for 4h, the calcination temperature is 650℃, the heating rate is 4℃ / min, and the temperature is kept for 2h. After cooling, silica fiber is obtained. Among them, the molecular weight of polyvinyl pyrrolidone is 120-150W, and the amount added accounts for 1-2wt% of the mixed solution, and the molecular weight of polyacrylamide is 120-140W, and the amount added accounts for 1-2wt% of the mixed solution.
[0043] An equal volume of 0.2 mol / L silver nitrate is added dropwise to a 0.1 mol / L sodium bicarbonate solution, and polyethylene glycol and sodium citrate are added after mixing evenly. The weight ratio of the mixed solution to polyethylene glycol and sodium citrate is 1:0.03 and 1:0.2 respectively. Stirring is continued until completely dissolved to obtain a silver-containing solution. Silica fiber is placed in a silver-containing solution, and the weight ratio of silica fiber to the silver-containing solution is 1:2.5. After a hydrothermal reaction in a high-pressure reaction device, nanosilver is loaded on the surface of the silica fiber. The conditions for the hydrothermal reaction are to heat to 250°C, a heating rate of 2°C / min, and keep warm for 10 hours.
[0044] The silica fibers loaded with nanosilver are spun into filter meshes for use.
[0045] (2) Finished tobacco products are treated with flavors and fragrances:
[0046] After the tobacco flavors and fragrances are prepared according to the product formula, they need to be transferred to the turnover tank, and the filter screen made of silica fiber loaded with nanosilver is installed at the feeding and discharging ports of the turnover tank. During the feeding and discharging process, the finished tobacco flavors and fragrances come into contact with the nanosilver, thereby achieving a sterilization effect. The antibacterial properties of the treated finished tobacco flavors and fragrances are tested, and the results are shown in Table 2.
[0047] The above tobacco flavors and fragrances are the same as those in Example 1. Of course, the present application is not limited thereto, and common products in the art may also be used instead.
[0048] (3) Recycling of antibacterial materials:
[0049] The filter screens made of silica fibers loaded with nano-silver at the feed and discharge ports of the turnover tank are regularly recovered, ultrasonically cleaned with water, propylene glycol and ethanol for 20-30 minutes respectively, and can be used again after drying.
[0050] Table 2 Antibacterial test results
[0051]
[0052] Example 3
[0053] (1) Preparation of antibacterial silica composite fiber material loaded with nanosilver:
[0054] By volume, 21 parts of tetraethyl orthosilicate, 19 parts of methanol, 1 part of N,N-dimethylformamide, and 0.1 parts of nitric acid solution are mixed, and polyvinyl pyrrolidone and polyacrylamide are added after stirring evenly, and stirring is continued for more than 2 hours to prepare the spinning precursor solution. In the injection pump, the spinning precursor feed rate is 4mL / h, the voltage is 24kV, the curing acceptance distance is 18cm, and the inner diameter of the needle is 0.62cm. After the precursor solution is extracted, the drying conditions are vacuum drying at 100℃ for 4h, the calcination temperature is 600℃, the heating rate is 4℃ / min, and the temperature is kept for 2h. After cooling, silica fiber is obtained. Among them, the molecular weight of polyvinyl pyrrolidone is 120-150W, and the amount added accounts for 1-2wt% of the mixed solution, and the molecular weight of polyacrylamide is 120-140W, and the amount added accounts for 1-2wt% of the mixed solution.
[0055] An equal volume of 0.2 mol / L silver nitrate is added dropwise to a 0.1 mol / L sodium bicarbonate solution, and polyethylene glycol and sodium citrate are added after mixing evenly. The weight ratio of the mixed solution to polyethylene glycol and sodium citrate is 1:0.04 and 1:0.5 respectively. Stirring is continued until completely dissolved to obtain a silver-containing solution. Silica fiber is placed in a silver-containing solution, and the weight ratio of silica fiber to the silver-containing solution is 1:3.5. After a hydrothermal reaction in a high-pressure reaction device, nanosilver is loaded on the surface of the silica fiber. The conditions for the hydrothermal reaction are to heat to 250°C, a heating rate of 2°C / min, and keep warm for 10 hours.
[0056] The silica fibers loaded with nanosilver are spun into filter meshes for use.
[0057] (2) Finished tobacco products are treated with flavors and fragrances:
[0058] After the tobacco flavors and fragrances are prepared according to the product formula, they need to be transferred to the turnover tank, and the filter screen made of silica fiber loaded with nanosilver is installed at the feeding and discharging ports of the turnover tank. During the feeding and discharging process, the finished tobacco flavors and fragrances come into contact with nanosilver, thereby achieving a sterilization effect. The antibacterial properties of the treated finished tobacco flavors and fragrances are tested, and the results are shown in Table 3.
[0059] The above tobacco flavors and fragrances are the same as those in Example 1. Of course, the present application is not limited thereto, and common products in the art may also be used instead.
[0060] (3) Recycling of antibacterial materials:
[0061] The filter screens made of silica fibers loaded with nano-silver at the feed and discharge ports of the turnover tank are regularly recovered, ultrasonically cleaned with water, propylene glycol and ethanol for 20-30 minutes respectively, and can be used again after drying.
[0062] Table 3 Antibacterial test results
[0063]
[0064] Example 4
[0065] (1) Preparation of antibacterial silica composite fiber material loaded with nanosilver:
[0066] By volume, 24 parts of tetraethyl orthosilicate, 16 parts of methanol, 1 part of N,N-dimethylformamide, and 0.1 parts of nitric acid solution are mixed, and polyvinyl pyrrolidone and polyacrylamide are added after stirring evenly. Stirring continues for more than 2 hours to prepare the spinning precursor solution. In the injection pump, the spinning precursor feed rate is 3-6mL / h, the voltage is 25kV, the curing acceptance distance is 18cm, and the inner diameter of the needle is 0.62cm. After the precursor solution is extracted, the drying conditions are vacuum drying at 100℃ for 4h, the calcination temperature is 580℃, the heating rate is 4℃ / min, and the temperature is kept for 2h. After cooling, silica fiber is obtained.
[0067] Add an equal volume of 0.2 mol / L silver nitrate to a 0.1 mol / L sodium bicarbonate solution, mix well, add polyethylene glycol and sodium citrate, polyethylene glycol and sodium citrate, the weight ratio of the mixed solution to polyethylene glycol and sodium citrate is 1:0.05 and 1:0.6 respectively, continue stirring until completely dissolved, and a silver-containing solution is obtained. Place silica fiber in a silver-containing solution, the weight ratio of silica fiber to silver-containing solution is 1:5, and after hydrothermal reaction in a high-pressure reaction device, nanosilver is loaded on the surface of silica fiber. The conditions of the hydrothermal reaction are to heat to 250°C, the heating rate is 2°C / min, and keep warm for 10 hours.
[0068] The silica fibers loaded with nanosilver are spun into filter meshes for use.
[0069] (2) Finished tobacco products are treated with flavors and fragrances:
[0070] After the tobacco flavors and fragrances are prepared according to the product formula, they need to be transferred to the turnover tank, and the filter screen made of silica fiber loaded with nanosilver is installed at the feeding and discharging ports of the turnover tank. During the feeding and discharging process, the finished tobacco flavors and fragrances come into contact with the nanosilver, thereby achieving a sterilization effect. The antibacterial property of the treated finished tobacco flavors and fragrances is tested, and the results are shown in Table 4.
[0071] The above tobacco flavors and fragrances are the same as those in Example 1. Of course, the present application is not limited thereto, and common products in the art may also be used instead.
[0072] (3) Recycling of antibacterial materials:
[0073] The filter screens made of silica fibers loaded with nano-silver at the feed and discharge ports of the turnover tank are regularly recovered, ultrasonically cleaned with water, propylene glycol and ethanol for 20-30 minutes respectively, and can be used again after drying.
[0074] Table 4 Antibacterial test results
[0075]
[0076] Although the present invention has been disclosed as above by the embodiments, it is not intended to limit the present invention. Any person skilled in the art may make various choices and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention is limited by the claims and their equivalents.
Claims
1. A nanosilver-loaded silica composite fiber antibacterial material, characterized in that: The invention comprises a silicon dioxide fiber carrier and loaded nano silver, wherein the nano silver is loaded on the surface of the silicon dioxide fiber carrier, and the loading amount of the nano silver is 0.05-0.5%.
2. The nanosilver-loaded silica composite fiber antibacterial material according to claim 1, characterized in that: The silica fiber carrier is prepared by an electrostatic spinning method.
3. A method for preparing a nanosilver-loaded silica composite fiber antibacterial material, characterized in that: The following steps are involved: (1) Preparation of silica fiber: a certain amount of tetraethyl orthosilicate, methanol, N,N-dimethylformamide and nitric acid solution are mixed, polyvinyl pyrrolidone and polyacrylamide are added after stirring evenly, and stirring is continued for more than 2 hours to obtain an electrospinning precursor solution, and the spinning precursor solution is extracted in a micro-syringe pump, dried and then calcined, and the silica fiber is obtained after cooling; (2) Preparation of silver-containing solution: Add an equal volume of 0.2 mol / L silver nitrate dropwise to a 0.1 mol / L sodium bicarbonate solution, mix well, add polyethylene glycol and sodium citrate, and continue stirring until completely dissolved to obtain a silver-containing solution; (3) Preparation of nanosilver-loaded silica composite fiber antibacterial material: The silica fiber of step (1) is placed in the silver-containing solution of step (2), placed in a high-pressure reaction device, and subjected to a hydrothermal reaction to obtain the nanosilver-loaded silica composite fiber antibacterial material.
4. The method for preparing the nanosilver-loaded silica composite fiber antibacterial material according to claim 3, characterized in that: The following steps are also included: (5) Molding treatment: The obtained nanosilver-loaded silica fibers are prepared into a spun filter for use.
5. The method for preparing the nanosilver-loaded silica composite fiber antibacterial material according to claim 3, characterized in that: In step (1), the volume ratio of tetraethyl orthosilicate, methanol, N,N-dimethylformamide and nitric acid solution is (20-25):(15-20):1:0.1, the concentration of nitric acid is 0.1-0.4 mol / L, the molecular weight of polyvinyl pyrrolidone is 120-150W, and the added amount accounts for 1-2wt% of the mixed solution, and the molecular weight of polyacrylamide is 120-140W, and the added amount accounts for 1-2wt% of the mixed solution.
6. The method for preparing the nanosilver-loaded silica composite fiber antibacterial material according to claim 3, characterized in that: In step (1), the parameters of the precursor liquid spinning in the syringe pump are: the spinning precursor liquid feeding speed is 3-6mL / h, the voltage is 23-26kV, the solidification acceptance distance is 18cm, and the inner diameter of the needle is 0.62cm.
7. The method for preparing the nanosilver-loaded silica composite fiber antibacterial material according to claim 3, characterized in that: In step (1), after the precursor solution is extracted, the drying conditions are vacuum drying at 100°C for 4 hours, the calcination temperature is 550°C-650°C, the heating rate is 4°C / min, and the temperature is kept for 2 hours.
8. The method for preparing the nanosilver-loaded silica composite fiber antibacterial material according to claim 3, characterized in that: In step (2), the weight ratio of the mixed solution to polyethylene glycol and sodium citrate is 1:0.01-0.05 and 1:0.1-0.6 respectively; in step (3), the weight ratio of the silica fiber to the silver-containing solution is 1:2-5.
9. Application of a nanosilver-loaded silica composite fiber antibacterial material in the sterilization of tobacco flavors and fragrances, characterized in that: The nano-silver loaded silica composite fiber antibacterial material is a nano-silver loaded silica composite fiber antibacterial material prepared according to any one of the preparation methods described in claims 3-8.
10. Application of a nanosilver-loaded silica composite fiber antibacterial material in the sterilization of tobacco flavors and fragrances, characterized in that: The application is: tobacco flavors and fragrances are transferred into a turnover tank, and a filter mesh made of silica fiber loaded with nano-silver is installed at the feed port and the discharge port of the turnover tank. The finished tobacco flavors and fragrances are in contact with the nano-silver during the feeding and discharging process, thereby achieving a sterilization effect. The filter mesh made of silica fiber loaded with nano-silver at the feed port and the discharge port of the turnover tank is regularly recovered, ultrasonically cleaned with water, propylene glycol and ethanol for 20-30 minutes respectively, and then continued to be used after drying.